2016
DOI: 10.1089/aid.2015.0020
|View full text |Cite
|
Sign up to set email alerts
|

Full Length Single Chain Fc Protein (FLSC IgG1) as a Potent Antiviral Therapy Candidate: Implications forIn VivoStudies

Abstract: We have previously shown that FLSC, a chimeric protein containing HIV-1 BAL gp120 and the D1 and D2 domains of human CD4, blocks the binding and entry of HIV-1 into target cells by occluding CCR5, the major HIV-1 coreceptor. In an effort to improve the antiviral potential of FLSC, we fused it with the hinge-C H 2-C H 3 region of human IgG1. The IgG moiety should increase both the affinity and stability in vivo of FLSC, due to the resultant bivalency and an extended serum half-life, thereby increasing its antiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…with 20,000 of 50% tissue culture infective dose (TCID50%) of HIV-1 Bal, they developed a productive infection. 6 Quantifying CD4+ T cells, CCR5+ cells, and CCR5 expression levels to evaluate and validate the NSG adult mouse model, we showed that levels of both CD4+ and CCR5+ cells from within the CD4+ T cell population remained stable in non-infected mice up to 4 weeks post engraftment. 6 As expected, infected mice showed a steep decline in CD4+ T cells and CCR5+ cells, as well as somewhat reduced CCR5 expression levels.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…with 20,000 of 50% tissue culture infective dose (TCID50%) of HIV-1 Bal, they developed a productive infection. 6 Quantifying CD4+ T cells, CCR5+ cells, and CCR5 expression levels to evaluate and validate the NSG adult mouse model, we showed that levels of both CD4+ and CCR5+ cells from within the CD4+ T cell population remained stable in non-infected mice up to 4 weeks post engraftment. 6 As expected, infected mice showed a steep decline in CD4+ T cells and CCR5+ cells, as well as somewhat reduced CCR5 expression levels.…”
Section: Discussionmentioning
confidence: 94%
“…6 Quantifying CD4+ T cells, CCR5+ cells, and CCR5 expression levels to evaluate and validate the NSG adult mouse model, we showed that levels of both CD4+ and CCR5+ cells from within the CD4+ T cell population remained stable in non-infected mice up to 4 weeks post engraftment. 6 As expected, infected mice showed a steep decline in CD4+ T cells and CCR5+ cells, as well as somewhat reduced CCR5 expression levels. 6 A second approach, based upon the injection of HSC into newborn mice supports longer-term experiments and allows multilineage development of human immune cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Both cell lines showed a decrease in mAb binding to CCR5 when cells were pretreated with full length single chain IgG1 (FLSC IgG1), a chimeric protein containing HIV-1 BaL gp120 and the D1 and D2 domains of human CD4. FLSC IgG1 competitively binds the coreceptor at two different regions, the NT and ECL2 [ 17 , 18 ]. As expected, the visualized CCR5 signal was correspondingly lower in the JC10 cell line due to lower CCR5 expression (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that dimerization of CCR5 contributes to the conformational diversity of G-protein coupled receptors (GPCRs), which is a promising avenue of research for the prevention of HIV-1 entry [ 13 ]. Recognition of CCR5’s role has led to the development of effective antiviral drugs, including CCR5 antagonists and inverse agonists such as Maraviroc (MVC) [ 14 16 ] and fusion proteins that target the NT and other relevant sites in CCR5 [ 17 , 18 ], as well as various anti-CCR5 antibodies [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%